2012
DOI: 10.1007/s10658-012-0066-6
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge on plant/canopy architectural traits that reduce the expression and development of epidemics

Abstract: To reduce the use of pesticides, innovative studies have been developed to introduce the plant as the centre of the crop protection system. The aim of this paper is to explain how architectural traits of plants and canopies induce a more or less severe epidemic and how they may be modified in order to reduce disease development. In particular, it focuses on three key questions: i) which processes linked to epidemics can be influenced by architecture ii) how can architecture be characterized relative to these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 45 publications
0
36
0
7
Order By: Relevance
“…It is also influenced by canopy architecture and of host receptivity to infection over time, therefore raising three primary questions: (i) can architecture modify inoculum interception, (ii) how does architecture drive the occurrence of microclimatic conditions favorable to disease development, and (iii) can architecture change the dynamics of tissue receptivity? (Tivoli et al, 2013). Leaf density measured through the leaf area index (LAI) had an effect on the physiological barrier increasing with canopy LAI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also influenced by canopy architecture and of host receptivity to infection over time, therefore raising three primary questions: (i) can architecture modify inoculum interception, (ii) how does architecture drive the occurrence of microclimatic conditions favorable to disease development, and (iii) can architecture change the dynamics of tissue receptivity? (Tivoli et al, 2013). Leaf density measured through the leaf area index (LAI) had an effect on the physiological barrier increasing with canopy LAI.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects were observed for Colletotrichum acutatum on strawberry (Yang et al, 1990;Madden et al, 1993), suggesting that the physiological barrier effect is a major plant architectural phenomenon that influences a wide range of pathosystems. In apple trees, Tivoli et al (2013) suggested that some trimming systems led to a higher aeration and therefore shorter periods of wetness, hence less apple scab infection (Venturia inaequalis). Generally, it can be concluded that plant canopy architecture unfavorable to an aerial epidemic may result in the total avoidance of disease, but more frequently reduces disease severity rather than preventing infection completely.…”
Section: Introductionmentioning
confidence: 99%
“…WM resistance in the field is a trait of complex inheritance, which includes physiological resistance and disease avoidance (Fuller et al 1984, Schwartz et al 1987, Kim and Diers 2000, Kolkman and Kelly 2002, Miklas et al 2013). In general, WM avoidance is associated with morphological and phenological traits, such as upright plant architecture, lodging resistance, canopy porosity and height, and maturity (Miklas et al 2013, Tivoli et al 2013, and these traits are highly influenced by the environment (Teixeira et al 1999, Miklas et al 2013, Moura et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Notably, BRS Esplendor has upright and BRS Executivo semi-upright plant architecture ( Table 1), traits that favor avoidance of WM in the field (Tivoli et al 2013, Miklas et al 2013. In Goianira, BRS Embaixador, BRS Radiante, BRS Realce, and Jalo Precoce showed significant and negative effects on WM severity, with approximately the same magnitude.…”
Section: Lu Ferreira Et Almentioning
confidence: 95%
“…A influência da arquitetura de plantas sobre o desenvolvimento de epidemias é uma linha de pesquisa recente, mas que tem obtido resultados promissores, podendo ser uma das ferramentas a ser incorporada no manejo de doenças de plantas (Tivoli et al, 2013).…”
Section: Introductionunclassified